PELATIHAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN EMPATI PESERTA DIDIK DENGAN MENGGUNAKAN E-COMIC PADA GURU-GURU SEKOLAH INDONESIA CAIRO (SIC) - Awaluddin Tjalla; Wirda Hanim; Nina Nurhasanah (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract Teachers in basic education units at the Indonesian Elementary School and Junior High School Cairo (SIC) need the skills to carry out group guidance activities in fostering the empathetic character of students. The existence of covid 19 causes learning to be carried out only face-to-face, so it is difficult for students to develop an empathetic character. The solution offered is to train teachers in the form of workshops to be skilled at providing group guidance interventions using E-Comic media. The implementation of community service consists of: 1) Focus Group Discussion (FGD 1), 2) Workshop, 3) Focus Group Discussion (FGD 2), and 4) Development of E-Comic. The method used is the Workshop and Focus Group Discussion, as well as the practice of making E-Comic story materials. Participants in the activity consisted of principals and SIC teachers in Egypt. Through the workshop, the result received is the ability of teachers to make E-Comic story materials about empathy to be used by elementary and junior high school students to increase empathy. By conducting community service activities through Workshops and Focus Group Discussions, elementary and junior high school teachers at the Indonesian School of Cairo gain knowledge and skills in making E-Comic story materials that will be used for making E-Comic in increasing the empathetic character of students. Abstrak Para guru pada satuan pendidikan dasar di Sekolah Dasar dan Sekolah Menengah Pertama Sekolah Indonesia Cairo (SIC) memerlukan keterampilan melakukan kegiatan bimbingan kelompok dalam menumbuhkan karakter empati peserta didik. Adanya covid 19 menyebabkan pembelajaran dilakukan dengan tatap maya, sehingga peserta didik sulit mengembangkan karakter empati. Solusi yang ditawarkan yaitu melatih para guru dalam bentuk workshop agar terampil memberikan intervensi bimbingan kelompok dengan menggunakan media E-Comic. Pelaksanaan pengabdian masyarakat terdiri dari: 1) Focus Group Discussion (FGD 1), 2) Workshop, 3) Focus Group Discussion (FGD 2), dan 4) Pengembangan E-Comic. Metode yang digunakan dengan Workshop dan Focus Group Discussion, serta praktik pembuatan bahan cerita E-Comic. Peserta kegiatan terdiri dari kepala sekolah, guru dan orang tua peserta didik di SIC Mesir. Melalui workshop, hasil yang diterima adalah meningkatnya kemampuan para guru membuat bahan cerita E-Comic mengenai empati untuk digunakan oleh peserta didik SD dan SMP dalam meningkatkan empati siswa. Dengan melakukan kegiatan pengabdian masyarakat melalui Workshop dan Focus Group Discussion para guru SD dan SMP Sekolah Indonesia Cairo mendapatkan pengetahuan dan keterampilan dalam membuat bahan cerita E-Comic yang akan digunakan untuk pembuatan E-Comic dalam meningkatkan karakter empati peserta didik.